1992
DOI: 10.2214/ajr.159.4.1326885
|View full text |Cite
|
Sign up to set email alerts
|

CT arterial portography: causes of technical failure and variable liver enhancement.

Abstract: Technical failures and enhancement variability are common in CT arterial portography. Factors leading to technical failure include catheter choice and position, portal hypertension, and operator error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 15 publications
0
22
1
Order By: Relevance
“…The fact that technical failures have been implicated in this false-positive rate does not alter the decreasing efficacy of this method to accurately predict unresectability before operation. 15 The use of HAPS in this study did not improve either the positive predictive value for predicting unresectability (60%) or the sensitivity (83%) compared with CTAP. Although CTAP accurately detects most lesions found at surgery, the HAPS study predicts tumor that is not found at surgery, that is only found at blind resection or blind biopsy, and may even not be detected until months after operation.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The fact that technical failures have been implicated in this false-positive rate does not alter the decreasing efficacy of this method to accurately predict unresectability before operation. 15 The use of HAPS in this study did not improve either the positive predictive value for predicting unresectability (60%) or the sensitivity (83%) compared with CTAP. Although CTAP accurately detects most lesions found at surgery, the HAPS study predicts tumor that is not found at surgery, that is only found at blind resection or blind biopsy, and may even not be detected until months after operation.…”
Section: Discussioncontrasting
confidence: 53%
“…Its limitations, however, are the imaging ofrelatively isodense and/or small (less than 1 to 2 cm) lesions, visualization of extrahepatic disease, and the inability to distinguish between benign from malignant tumors.6'7 The decreased sensitivity of CT to detect metastatic lesions has not been improved with magnetic resonance imaging, although the latter accurately diagnoses lesions such as hemangiomas and cysts.8 Many recent reviews have documented the efficacy ofCT angiography (superior mesenteric arterial portography) in detecting small hepatic lesions not seen by standard CT.6'7'9-'3 The increased sensitivity (80% to 90%) of CT arterial portography (CTAP) has been associated with increased false-positive diagnoses because of flow artifacts, cysts, small benign tumors, and in some cases no lesions detected. [14][15][16] A natural selection process exists because most patients referred for surgery and possible resection have been prescreened using the noninvasive techniques of CT and magnetic resonance imaging. Patients are often considered ineligible for surgery when the standard CT examination shows extensive, bilobar, or extrahepatic disease, which precludes resection for possible cure.…”
mentioning
confidence: 99%
“…Unfortunately, there is no published study evaluating CTHA or the combination of CTHA and CTAP techniques with explant correlation; therefore, their sensitivity for the detection of HCC and DN is unknown. In any event, these techniques are too invasive and costly to be used on a routine basis, may result in false-negative diagnoses of HCC when arterial anatomy is aberrant [35], and are subject to technical failure due to catheter position and operator error [36].…”
Section: Catheter Angiography Ct Hepatic Angiography and Ct During Amentioning
confidence: 99%
“…Paulson et al [27] reported such technical failures in 26% of patients. Causes of failure included catheter dislodgement either during transportation of the patient or during injection with recoil into the aorta, dense hyperenhancement of portions of liver due to laminar flow, reflux of contrast into a replaced right hepatic artery, and portal hypertension.…”
mentioning
confidence: 98%